Connectedness to the criminal community and the community at large predicts 1‐year post‐release outcomes among felony offenders. (13th October 2015) - Folk, Johanna B.; Mashek, Debra; Tangney, June; Stuewig, Jeffrey; Moore, Kelly E.
Abstract: Connectedness to one's community relates to positive psychological and behavioral outcomes. But what implications do connectedness to distinct communities—the criminal community and the community at large—have for inmates about to be released from jail? This study ( N = 383) prospectively examined connectedness to the criminal community and community at large prior to release from jail and functioning at 1‐year post‐release. Connectedness to the community at large positively predicted community adjustment, whereas connectedness to the criminal community positively predicted recidivism. Targeting both types of community connectedness may enhance interventions intended to undermine recidivism and increase positive outcomes for inmates.